2015
DOI: 10.1177/1535370215598401
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates renal injury and fibrosis by inhibiting transforming growth factor-β pathway on matrix metalloproteinase 7

Abstract: Renal injury has a strong relationship to the subsequent development of renal fibrosis. In developing renal fibrosis, tubular epithelial cells in the kidney underwent epithelial-mesenchymal transition (EMT). Matrix metalloproteinase 7 (MMP7) was reported to reduce E-cadherin and induce EMT by up-regulation of β-catenin/lymphoid enhancer-binding factor 1 (LEF1) signaling. In this research, we tried to evaluate the role of resveratrol (RSV) on EMT process in renal injury and fibrosis. Human tubular epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 34 publications
2
64
0
3
Order By: Relevance
“…Finally, we have found that resveratrol is protective against ROS damage in part by increasing antioxidant production via a Sirt1 mediated mechanism, which suppresses apoptotic signaling from intrinsic and extrinsic mediated pathways, although the intrinsic mitochondrial pathway appears to be more important in myoblasts under a high ROS load. Our data are consistent with studies that have shown that resveratrol mediates antioxidant and anti-apoptotic protection against pathologies including renal cell damage [70], ischemia in neural cells [44], and ischemia-reperfusion in cardiac cells [71], and skeletal muscle cells [18]. We cannot rule out the possibility that myoblasts and myotubes may have different capabilities or regulation of their antioxidant systems with or without resveratrol treatment [22].…”
Section: Resultssupporting
confidence: 90%
“…Finally, we have found that resveratrol is protective against ROS damage in part by increasing antioxidant production via a Sirt1 mediated mechanism, which suppresses apoptotic signaling from intrinsic and extrinsic mediated pathways, although the intrinsic mitochondrial pathway appears to be more important in myoblasts under a high ROS load. Our data are consistent with studies that have shown that resveratrol mediates antioxidant and anti-apoptotic protection against pathologies including renal cell damage [70], ischemia in neural cells [44], and ischemia-reperfusion in cardiac cells [71], and skeletal muscle cells [18]. We cannot rule out the possibility that myoblasts and myotubes may have different capabilities or regulation of their antioxidant systems with or without resveratrol treatment [22].…”
Section: Resultssupporting
confidence: 90%
“…Specifically, in lung and ovarian cancers, SIRT1 was shown to repress EMT via cell migration inhibition [41,42]. Furthermore, SIRT1 upregulation, through resveratrol treatment, inhibited EMT in renal injury and fibrosis [43]. In the same vein, we found that SIRT1 downregulation, due to lactate exposure or NAM treatment, increased N-cadherin and vimentin expression in RCC cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…MMP-7 over-expression regulates chemokine gradients that can lead to severe tissue damage through transepithelial influx of neutrophils [59]. In an in vitro and in vivo study, resveratrol reversed the injury of human epithelial cells and attenuated such injury in mice through the inhibition of MMP-7 expression [60]. Kinase Insert Domain Receptor (KDR) (or Vascular Endothelial Growth Factor Receptor-2, VEGFR2) is a key receptor that promotes Vascular Endothelial Growth Factor (VEGF) to form mitosis and generate vascularization.…”
Section: Discussionmentioning
confidence: 99%